Financial Management Flexibility and Public Service Performance in Indonesian Public Hospitals - Susi Sugiyarsih (Sultan Publisher, 2024)
Public hospitals are an inseparable part of the provision of health services and improvement of community welfare. With the increasing demand for health services, hospitals are required to manage financial resources efficiently but still maintaining the quality of service and organizational accountability. In Indonesia, the financial management system of the BLU has been introduced to provide greater flexibility in financial management and improve the efficiency of public service delivery. This study investigates the relationship between financial management flexibility and public service performance in Indonesian public hospitals. This study adopts a narrative literature review approach. It reviews academic publications, government regulations, policy documents and literature related to hospital financial management, public sector governance and healthcare service performance. The literature collected was reviewed for the contribution of financial flexibility on operational efficiency, resource utilization, accountability, and service quality in public hospitals. The discussion points to flexible financial management as a way for hospitals to better meet operational needs, improve resource use and improve service delivery. The BLU financial management system allows more autonomy in financial decision making within the requirements of accountability. However, the issues of governance capacity, financial control, organizational management and service quality monitoring continue to influence the effectiveness of implementation. The study concludes that financial management flexibility is important instrument to improve public service performance of Indonesian public hospitals. Enhancing governance practices, accountability mechanisms and managerial capacity is still critical to ensure that financial flexibility leads to sustainable improvement of healthcare services.